CHI '06 Extended Abstracts on Human Factors in Computing Systems 2006
DOI: 10.1145/1125451.1125592
|View full text |Cite
|
Sign up to set email alerts
|

Low-fi prototyping for mobile devices

Abstract: This paper introduces a set of concepts for usercentered design methodologies that apply to mobile and multi-device applications. It ranges from initial data gathering and specification processes to the creation of low-fidelity prototypes and their evaluation. The focus is given to usability issues of ubiquitous, context and ambient intelligent applications. The paper's main contributions are (1) the description of our findings on how to engage on the early stage prototyping process, involving mobility; (2) a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…Design methods, techniques and tools for mobile devices are increasingly being addressed by researchers, leading to the appearance of different approaches for a wide range of problems [4,14,15,8]. Unsurprisingly, given their differences from desktop systems, most efforts have been directed towards prototyping and evaluation.…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations
“…Design methods, techniques and tools for mobile devices are increasingly being addressed by researchers, leading to the appearance of different approaches for a wide range of problems [4,14,15,8]. Unsurprisingly, given their differences from desktop systems, most efforts have been directed towards prototyping and evaluation.…”
Section: Related Workmentioning
confidence: 99%
“…Regarding prototyping, new techniques and orientations, particularly for low-fidelity prototypes, have been introduced [14,15]. These suggest the need for more detailed and carefully built prototypes that offer resembling pictures of final solutions and their characteristics [14], even at very early stages [17,18].…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…De Sá and Carriço (de Sá and Carriço, 2006) showed that prototyping techniques can be determinant during the consequent evaluation stages, allowing users to freely interact with the system, improve them and use them on realistic settings without being misled. In this section, we introduce a technique for the early-stage evaluation of interaction obtrusiveness adaptation of services by means of fast-prototyping.…”
Section: Simulationmentioning
confidence: 99%